Tanaisia (Tamerlania) zarudnyi vietnamensis odening, 1963 (eucotylidae: trematoda) from the red jungle fowl Gallus gallus spadiceus in Peninsular Malaysia - Lee, C. C.; Krishnasamy, M.; Babjee, Shaik Mohamed Amin; Dunsmore, J. D. (Malaysian Society of Parasitology and Tropical Medicine, 1985)
Tanaisia zarudnyi vietnamensis Odening, 1963 is described in detail from a new host Gallus gallus spadiceus (the red jungle fowl). This species of fluke was first reported in Garrulax chinensis from Vietnam. The flukes in this study were recovered from the collecting ducts and ureter of the kidney in 10 out of 14 red jungle fowls examined. Some measurements and description of the parasite are provided. The intermediate host for the parasite is also postulated G. g. spadiceus is a new host record for T. z. vietnamensis in Malaysia.